1962
DOI: 10.1177/00220345620410021201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Hulls and Other Seed Hulls on Dental Caries Production in the Cotton Rat

Abstract: While studying natural diets which were cariogenic to the cotton rat, Constant, Sievert, Phillips, and Elvehjem1 found that the degree of dental caries produced by an oatmeal diet was sharply decreased by the inclusion of finely ground oat hulls in the diet. The protective effect was greater at the 25 per cent level than at the 12.5 per cent level. Later work by Taketa and Phillips2 demonstrated that oat hulls were also protective in a semipurified diet at both 25 and 10 per cent levels. These workers furnishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These studies revealed an increased caries incidence with decreased intake of IP6 following changes in dietary habits and food processing and refinement (Jenkins et al, 1959a;Jenkins et al, 1959b;Jenkins, 1966). Several early studies showed a reduction of experimental caries in animals fed dietary IP6 (Taketa and Phillips, 1957;Buttner and Muhler, 1959;McClure, 1960;Madsen and Edmonds, 1962;Vogel et al, 1962;McClure, 1963;McClure, 1964;Dawes and Shaw, 1965;Englander and Keyes, 1970;Cole et al, 1980); however, these findings were not corroborated by other researchers, where IP6 had limited or no protective influence (Limbasuta et al, 1961;König and Grenby, 1965;Grenby, 1966;Lllienthal et al, 1966). The cariostatic mechanism of IP6 is not fully understood, although several pathways have been suggested.…”
Section: Oral Care Productsmentioning
confidence: 99%
“…These studies revealed an increased caries incidence with decreased intake of IP6 following changes in dietary habits and food processing and refinement (Jenkins et al, 1959a;Jenkins et al, 1959b;Jenkins, 1966). Several early studies showed a reduction of experimental caries in animals fed dietary IP6 (Taketa and Phillips, 1957;Buttner and Muhler, 1959;McClure, 1960;Madsen and Edmonds, 1962;Vogel et al, 1962;McClure, 1963;McClure, 1964;Dawes and Shaw, 1965;Englander and Keyes, 1970;Cole et al, 1980); however, these findings were not corroborated by other researchers, where IP6 had limited or no protective influence (Limbasuta et al, 1961;König and Grenby, 1965;Grenby, 1966;Lllienthal et al, 1966). The cariostatic mechanism of IP6 is not fully understood, although several pathways have been suggested.…”
Section: Oral Care Productsmentioning
confidence: 99%
“…It is generally accepted that carbohydrates with low molecular weights, such as sucrose, are easily fermentable and therefore highly cariogenic (Newburn, 1982; Leach et al, 1983). Of particular relevance to the study of dental health in Southeast Asian populations is the relatively cariostatic nature of rice (Madsen and Edmonds, 1962). A clinical study has shown that parboiled rice resulted in one of the smallest increases in acidity when compared with sucrose and carbohydrate rich foods like potatoes and wheat bread (Lingström et al, 1993).…”
Section: Dental Caries and Southeast Asiamentioning
confidence: 99%
“…The anticaries effect of oat hulls was coniirmed by Madsen (1958), Taketa McDonald (I 974) using rodent models given cariogenic diets comprising moderate and high percentages of mono-and disaccharides. Other seed hulls including those of barley, cocoa, cottonseed, peanut, pecan, soya bean and s d o w e r have also been shown to confer an anticaries effect on cariogenic diets in the cotton-rat model (Madsen & Edmonds, 1962). It is suggested that the anticaries effect is induced by the polyphenols present in the hulls exerting an antibacterial or an antidemineralization role.…”
Section: Dietary Elements Inhibiting Decaymentioning
confidence: 99%